Inquisitiveness: distributing rational thinking. Issue 1 (14th March 2017) - Bardone, Emanuele; Secchi, Davide
Abstract : Purpose: This study aims at redefining bounded rationality on the basis of a more socialized view of the individual. In doing so, it introduces "inquisitiveness" as a key disposition that some team members use to assemble and integrate knowledge when solving problems. Design/methodology/approach: Using an agent-based computational simulation, this research models different simulated employees working together in "ad hoc" teams to solve problems. Findings: Results show that inquisitiveness may work as an efficiency "driver" that, when present, economizes on the knowledge needed by team members to solve problems. In addition to that, results also show that environments with many problems are more suitable for inquisitive individuals to be effective. Originality/value: Following the late Herbert Simon, the paper takes the stance that rationality should be redefined as a socially oriented process and introduces inquisitiveness as one – although probably not the only one – of the characteristics that help individuals and teams to make rational decisions.